MEMBANGUN BISNIS FILANTROPI YANG BERETIKA: STRATEGI PERLINDUNGAN KONSUMEN DAN PENCEGAHAN PENYELEWENGAN DANA DALAM PERSPEKTIF HUKUM PERDATA DAN HUKUM TATA NEGARA - Dian Karisma; Rengga Kusuma Putra; Satriya Nugraha; Linda Ikawati; Bagus Hermanto (Fiat Iustitia : Jurnal Hukum, 2025)
Philanthropy which is a voluntary action aimed at enhancing social welfare, faces significant challenges related to the misuse of funds that can undermine public trust. Regulatory weaknesses, particularly Law No. 9 of 1961, demonstrate inadequacies in accommodating the developments of modern philanthropy, such as digital fundraising. Consumer protection in the context of Civil Law must encompass clear regulations regarding the rights and responsibilities between donors, managers, and beneficiaries, while Constitutional Law emphasizes the need for a robust constitutional framework to oversee philanthropic activities. Collaboration between the state, regulatory bodies, and civil society is crucial for creating a transparent and accountable system. The utilization of Indonesia's demographic and cultural potential, with the value of mutual assistance as a foundation, can support income redistribution and sustainable community empowerment, thereby ensuring that philanthropy effectively contributes to enhancing social welfare.